Faktor-Faktor Yang Mempengaruhi Nilai Konstruksi Di Indonesia Dengan Regresi Poisson dan Regresi Binomial Negatif - Juan Sheptiadi Efendi; Rahmadi Yotenka (Unisda Journal of Mathematics and Computer Science (UJMC), 2021)
Abstract. The construction sector is one of the drivers of national economic growth, contributing 10.6% to the National GDP. The capitalization value of the construction sector continues to increase from year to year due to an increase in the industrial sector in the private sector and infrastructure acceleration programs launched by the government in several provinces. However, this has led to a lack of equitable distribution of infrastructure development in several other provinces. To help the government carry out equitable infrastructure development, which can then help the national economy, an analysis is needed to find out what factors affect the construction value of each province in Indonesia. The relationship between the value of the construction and the factors that influence it can be determined by regression analysis. The regression analysis method used in this study is Poisson regression and negative binomial regression. Negative binomial regression is performed specifically to overcome overdispersion in Poisson regression. After the analysis, the results of the factors that have a statistical influence on the value of construction in Indonesia (NK) are the number of workers in each province (JTK) and the number of construction companies in each province (JP) with a pseudo R2 value of 0.978 or 97.8%.